2008
DOI: 10.3171/foc/2008/24/6/e9
|View full text |Cite
|
Sign up to set email alerts
|

Brain abscess: analysis of results in a series of 51 patients with a combined surgical and medical approach during an 11-year period

Abstract: Object In this study the authors' goal was to present the clinical and imaging results of the combined surgical and medical treatment of intracranial abscesses. Methods The authors retrospectively analyzed the data in 51 patients with intracranial abscesses who underwent surgery between January 1997 and November 2007. Patients were treated with aspiration through a single bur hole, total resection with o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
105
5
6

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 86 publications
(123 citation statements)
references
References 17 publications
7
105
5
6
Order By: Relevance
“…[31][32][33][34][35][36][37][38] Brain abscesses were singular in 77.7% of the subjects and multiple in 22.3%, a result similar to that reported by Landriel et al [39] The frontal lobe was the most common abscess location in the patients, followed by the temporal and occipital regions. However, in a study carried out by Cavusoglu et al, [40] the temporoparietal region was the most commonly affected location. Abscesses of unknown cause accounted for 54.94% of the subjects, higher than the values reported for other series.…”
Section: Discussionmentioning
confidence: 91%
“…[31][32][33][34][35][36][37][38] Brain abscesses were singular in 77.7% of the subjects and multiple in 22.3%, a result similar to that reported by Landriel et al [39] The frontal lobe was the most common abscess location in the patients, followed by the temporal and occipital regions. However, in a study carried out by Cavusoglu et al, [40] the temporoparietal region was the most commonly affected location. Abscesses of unknown cause accounted for 54.94% of the subjects, higher than the values reported for other series.…”
Section: Discussionmentioning
confidence: 91%
“…Aspiration was repeated more than once in 30 of 32 (93%) patients who underwent aspiration in a series of 51 patients and only 10 patients underwent complete excision. 3) In another series, 19% of patients treated by aspiration underwent the procedure more than once. 5) A literature review spanning 78 years from 1930 to 2009 concluded that the high mortality from aspiration decreased dramatically after CT became available.…”
Section: Discussionmentioning
confidence: 98%
“…The anatomical location, number and size of abscesses, stage of abscess formation, and age and neurological status of the patient can influence the strategy for managing brain abscess. 3) Surgical treatment can involve either aspiration or excision of the abscess. The choice of procedure has been the subject of much debate.…”
Section: Introductionmentioning
confidence: 99%
“…Abscesses are treated surgically (by excision or drainage) whenever possible; indications to delay or avoid surgical excision include multiple distantly located abscesses, abscesses in deep or vital brain structures, and concurrent meningitis or ependymitis [16,18,19]. An additional indication to promptly perform surgery in the case reported here was the presence of obstructive hydrocephalus of the right lateral ventricle, as evidenced by severe ventricular dilation with periventricular T2 hyperintensity (consistent with interstitial edema) on the MRI.…”
Section: Discussionmentioning
confidence: 94%